Wayang’s Images Recognition using Vision Transformer - Sihananto, Andreas Nugroho; Al Haromainy , Muhammad Muharrom; Fauzi, Zaky Ahmad; Reza, Reno Alfa; Putra, Gredy Christian Hendrawan; Christianty, Theressa Marry (Universitas Pembangunan Nasional Veteran Jawa Timur, 2024)
Due to its complex nature and outdated perception, Wayang is a traditional Indonesian art form influenced by Hindu-Buddhism. However, it is difficult for the younger generation to recognize the various types of Wayang. In an effort to preserve Wayang culture, this study evaluates the performance of four deep learning models in recognizing types of Wayang namely, Vision Transformer (ViT), ResNet34, YOLOv5-cls, and YOLOv8-cls. These models were trained and assessed using a dataset of 232 images representing six Wayang types and using matrix such as accuracy, recall, precision, and F1 score. ViT demonstrated efficiency and adaptability despite high computational requirements, achieving the best accuracy (91.3%), showing high adaptability despite substantial computational requirements. Meanwhile, YOLOv5-cls and YOLOv8-cls offered a good balance betwwen accuracy and efficiency. This study suggest that deep learning models can play an essentialrole in Wayang by enhancing recognition accessibility, thus helping younger generations appreciate this tradisional art form.